INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE TEACHING OF SPECIAL SUBJECTS (Scientific journal of the Fergana State University, 2024)
This article will consider the theoretical model of the pedagogical system of the development and readiness of university teachers to use innovative pedagogical technologies in the higher education system. The relevance, theoretical significance and practical significance of the theoretical model under consideration are indicated. The relevance of the development of the theoretical model is due to the fact that it is an algorithm and Navigator in the sequence of performing actions and procedures in the organization of the educational process for developers and teachers of the additional education system. Theoretical and methodological foundations and conditions for the development of a theoretical model of a pedagogical system for the development and readiness of teachers of a technical university to use innovative pedagogical technologies in the system of further education are described.